Religious Education in England and Wales - Cole, W Ower (Journal of Dharma, 1984)
Religious education is the one compulsory subject on the curriculum of schools in England and Wales. However, whether it is taught at all in a particular school depends very largely upon the attitude of headmasters, and its effectiveness upon the skill, knowledge and enthusiasm of the teachers. In this latter respect it is on a par with all other subjects, of course. With regard to the former it serves to remind us that because a study of religion has to do With beliefs and values it is often subjected to unprofessional influences either from hostile atheists and indifferent agnostics or zealous adherents of one of the religions to be found in Britain today.